Music and Language in Social Interaction: Synchrony, Antiphony, and Functional Origins - Oesch, Nathan (Frontiers in Psychology, 2019)
Music and language are universal human abilities with many apparent similarities relating to their acoustics, structure, and frequent use in social situations. We might therefore expect them to be understood and processed similarly, and indeed an emerging body of research suggests that this is the case. But the focus has historically been on the individual, looking at the passive listener or the isolated speaker or performer, even though social interaction is the primary site of use for both domains. Nonetheless, an important goal of emerging research is to compare music and language in terms of acoustics and structure, social interaction and functional origins to develop parallel accounts across the two domains. Indeed, a central aim of both of evolutionary musicology and language evolution research is to understand the adaptive significance or functional origin of human music and language. An influential proposal to emerge in recent years has been referred to as the social bonding hypothesis. Here, within a comparative approach to animal communication systems, I review empirical studies in support of the social bonding hypothesis in humans, non-human primates, songbirds, and various other mammals. In support of this hypothesis, I review six research fields: (i) the functional origins of music; (ii) the functional origins of language; (iii) mechanisms of social synchrony for human social bonding; (iv) language and social bonding in humans; (v) music and social bonding in humans; (vi) pitch, tone and emotional expression in human speech and music. I conclude that the comparative study of complex vocalizations and behaviors in various extant species can provide important insights into the adaptive function(s) of these traits in these species, as well as offer evidence-based speculations for the existence of ‘musilanguage’ in our primate ancestors, and thus inform our understanding of the biology and evolution of human music and language.